PERAN PENGAWAS MENELAN OBAT (PMO) TUBERKULOSIS DALAM MENINGKATKAN KEPATUHAN MINUM OBAT PADA PASIEN TUBERKULOSIS PARU DI KELURAHAN SIDOMULYO BARAT PEKANBARU - Resmi Debby; Suyanto "; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The treatment observers is an important role for the success of DOTS strategy. Treatment observers is usually come from patients who will give a boost to the patient in order to improve patient compliance in taking medicine and regularing the treatment. TB cases in Pekanbaru city is still high with a low cure rate from the national average. This study is descriptive with a qualitative approach. The results showed a treatment role in improving medication adherence for patients with tuberculosis case is to accompany and supervise the patient every day, accompany the patient to the health center, remind patients to take medicine at night, give encouragement and support to patients, remind patients to examine repeated sputum, provide guidance to patients, and carry patients to doctor in case of side effects.Keyword: treatment observers, compliance, tuberculosis